2022
DOI: 10.1155/2022/7728973
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Evidence of Traditional Chinese Exercise (Qigong) for Chronic Obstructive Pulmonary Disease: An Overview of Systematic Reviews and Meta-Analyses

Abstract: Background. As a traditional Chinese exercise, Qigong has potential benefits for the management of chronic obstructive pulmonary disease (COPD). This overview is aimed at assessing the existing evidence for the intervention of Qigong in COPD so as to provide scientific guidance for clinical decision-making. Methods. The systematic reviews (SRs)/meta-analyses (MAs) of Qigong for the treatment of COPD were obtained from 7 electronic databases with the search date set at April 5, 2022. Two researchers independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Tis research was conducted according to the Cochrane Handbook and some high quality articles with scientifc research methodologies [16][17][18]. Tis overview protocol has been registered with the INPLASY website (Registration number: INPLASY202260077).…”
Section: Methodsmentioning
confidence: 99%
“…Tis research was conducted according to the Cochrane Handbook and some high quality articles with scientifc research methodologies [16][17][18]. Tis overview protocol has been registered with the INPLASY website (Registration number: INPLASY202260077).…”
Section: Methodsmentioning
confidence: 99%
“…Qigong is a kind of exercise, based on the principles of TCM, including breathing, movement, and meditation to stimulate health and well-being. It is used to treat various conditions like anxiety, depression, and stress (Shi et al, 2022).…”
Section: Exercise (Qigong)mentioning
confidence: 99%
“…It is a total body and mind movement that coordinates body posture, movement and breathing and has been used for thousands of years in China to promote health [ 19 – 20 ]. As a mind-body exercise, the key elements of Qigong are body movement, spiritual guidance and controlled breathing [ 21 22 ], and there are various forms of Qigong in China, including Tai Chi [ 23 ],Wuqinxi, Baduanjin, Yijinjing, and Liuzijue [ 24 ]. Previous studies have indicated that Qigong can enhance the cardiorespiratory endurance and flexibility of college students, reduce anxiety, alter their state of mind, and improve the psychological well-being, thus promoting the development of their physical and mental health [ 4 , 9 , 25 26 ].…”
Section: Introductionmentioning
confidence: 99%